Granulocyte-macrophage colony stimulatory factor enhances the pro-inflammatory response of interferon-γ-treated macrophages to pseudomonas aeruginosa infection - Singh, Sonali; Barr, Helen L.; Liu, Yi-Chia; Robins, Adrian; Heeb, Stephan; Williams, Paul; Fogarty, Andrew W.; Cámara, Miguel; Martinez-Pomares, Luisa (Public Library of Science, 2015)
Pseudomonas aeruginosa is an opportunistic pathogen that can cause severe infections at compromised epithelial surfaces, such those found in burns, wounds, and in lungs damaged by mechanical ventilation or recurrent infections, particularly in cystic fibrosis (CF) patients. CF patients have been proposed to have a Th2 and Th17-biased immune response suggesting that the lack of Th1 and/or over exuberant Th17 responses could contribute to the establishment of chronic P. aeruginosa infection and deterioration of lung function. Accordingly, we have observed that interferon (IFN)-γ production by peripheral blood mononuclear cells from CF patients positively correlated with lung function, particularly in patients chronically infected with P. aeruginosa. In contrast, IL-17A levels tended to correlate negatively with lung function with this trend becoming significant in patients chronically infected with P. aeruginosa. These results are in agreement with IFN-γ and IL-17A playing protective and detrimental roles, respectively, in CF. In order to explore the protective effect of IFN-γ in CF, the effect of IFN-γ alone or in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF), on the ability of human macrophages to control P. aeruginosa growth, resist the cytotoxicity induced by this bacterium or promote inflammation was investigated. Treatment of macrophages with IFN-γ, in the presence and absence of GM-CSF, failed to alter bacterial growth or macrophage survival upon P. aeruginosa infection, but changed the inflammatory potential of macrophages. IFN-γ caused up-regulation of monocyte chemoattractant protein-1 (MCP-1) and TNF-α and down-regulation of IL-10 expression by infected macrophages. GM-CSF in combination with IFN-γ promoted IL-6 production and further reduction of IL-10 synthesis. Comparison of TNF-α vs. IL-10 and IL-6 vs. IL-10 ratios revealed the following hierarchy in regard to the pro-inflammatory potential of human macrophages infected with P. aeruginosa: untreated < treated with GM-CSF < treated with IFN-γ < treated with GM-CSF and IFN-γ.